2012
DOI: 10.1634/theoncologist.2012-0007
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in Risk Prediction Between the 21-Gene Recurrence Score Assay (Oncotype DX®) and the PAM50 Breast Cancer Intrinsic Classifier™ in Early-Stage Estrogen Receptor–Positive Breast Cancer

Abstract: Purpose. To compare risk assignment by PAM50 Breast Cancer Intrinsic Classifier™ and Oncotype DX_Recur-rence Score (RS) in the same population.Methods. RNA was extracted from 151 estrogen receptor (ER) ؉ stage I-II breast cancers and gene expression profiled using PAM50 "intrinsic" subtyping test.Results. One hundred eight cases had complete molecular information; 103 (95%) were classified as luminal A (n ‫؍‬ 76) or luminal B (n ‫؍‬ 27). Ninety-two percent (n ‫؍‬ 98) had a low (n ‫؍‬ 59) or intermediate (n ‫؍‬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 23 publications
(17 reference statements)
1
41
0
2
Order By: Relevance
“…PAM50 is a quantitative real-time PCR (qRT-PCR)-based assay of 50 genes; it evolved from studies that have reproducibly demonstrated the prognostic significance and predictive ability of the four intrinsic subtypes of breast cancer Chia et al, 2012;Harvell et al, 2008;Kelly et al, 2012;Martín et al, 2013;Nielsen et al, 2010;Prat et al, 2014;Sorlie et al, 2001Sorlie et al, , 2003. Prosigna stratifies breast cancer patients who have been treated with surgery and endocrine therapy into risk groups regarding disease outcome for years 5-10 post surgery and endocrine therapy, which helps to reduce overtreatment with chemotherapy in patients with good prognosis (Parker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PAM50 is a quantitative real-time PCR (qRT-PCR)-based assay of 50 genes; it evolved from studies that have reproducibly demonstrated the prognostic significance and predictive ability of the four intrinsic subtypes of breast cancer Chia et al, 2012;Harvell et al, 2008;Kelly et al, 2012;Martín et al, 2013;Nielsen et al, 2010;Prat et al, 2014;Sorlie et al, 2001Sorlie et al, , 2003. Prosigna stratifies breast cancer patients who have been treated with surgery and endocrine therapy into risk groups regarding disease outcome for years 5-10 post surgery and endocrine therapy, which helps to reduce overtreatment with chemotherapy in patients with good prognosis (Parker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…98,99 Prosigna placed fewer patients into the intermediate-risk group than did Oncotype DX, potentially facilitating treatment decisions. 98,100 The assay is currently validated for postmenopausal women with HR þ , node-negative (stage I or II) or node-positive (stage II) disease. 101 Unlike some other MAAAs, Prosigna is not performed in a single, centralized laboratory, 95 but instead is performed in multiple reference laboratories, all using the same platform, probe library, and algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…From a purely scientific perspective there are some interesting observations about these expression profiles: firstly, although the intended clinical uses for some of the above tests seem quite similar and the gene signatures seem to have been identified in similar ways, the actual lists of genes included in the signatures show relatively little overlap (although maybe represent similar overall pathways) and the tests use rather different technical platforms (RT-PCR, microarray, NanoString) [17] ; secondly, the tests do not always identify exactly the same patients for classification as low or high risk for disease recurrence [18,19] . This could suggest that the utility of the tools derives not from a deep scientific understanding of the analytes (the genes, their relative degrees of expression and the actions of their products) nor even from a complete knowledge of the link between the underlying Clinical Validation • Sensitivity and specificity of the assay -clinical accuracy (in the intended patient population) • Assay failure rates (and reasons)…”
Section: Recent Successesmentioning
confidence: 99%